Fatty acid composition of the erythrocyte membrane and risk of hepatocellular carcinoma in cirrhotic patients. Issue 9 (11th August 2020) - Mouillot, Thomas; Rizk, Maud; Pais de Barros, Jean‐Paul; Gilloteau, Adrien; Busson, Amandine; Bernard‐Chabert, Brigitte; Thiefin, Gérard; Barraud, Hélène; Bronowicki, Jean‐Pierre; Richou, Carine; Di Martino, Vincent; Doffoel, Michel; et al.
Summary: Background: Disturbances in fatty acid (FA) metabolism have been reported in cirrhosis, but the role of FAs in the development of hepatocellular carcinoma (HCC) is still unclear. Biomarkers are a promising means to explore the associations between exogenous intake or endogenous production of FAs and cancer risk. Aim: To estimate the relationship between fatty acid content in erythrocyte membranes and HCC risk in cirrhotic patients Methods: The "CiRCE" case‐control study recruited cirrhotic patients from six French hospitals between 2008 and 2012. Cases were cirrhotic patients with HCC (n = 349); controls were cirrhotic patients without HCC at inclusion (n = 550). FA composition of phospholipids in erythrocyte membranes was determined by high performance gas chromatography. Odds ratios for HCC risk according to FA concentrations were estimated with multivariable logistic regression. Results: HCC patients were older and more often men ( P  < 0.001). In both groups, saturated FAs represented more than 39% of all FAs in erythrocyte membranes, mono‐unsaturated FAs around 14%, and polyunsaturated FAs around 46%. High levels of C15:0 + C17:0, C20:1 n‐9, C18:2 n‐6 and C20:2 n‐6 were associated with higher risk of HCC. The levels of C18:0 and C20:4 n‐6 were lower in HCC cases than in controls. Conclusions: The FA composition of erythrocyte membranes differed according to the presence of HCC with higher levels of saturated FAs, linoleic and eicosadienoic acids, and lower levels of stearic and arachidonic acids. These alterations may reflect particular dietary patterns and/or altered FA metabolism. Further investigations are warranted.